Critical data literacies rethinking data and everyday life - Pangrazio, Luci; Selwyn, Neil 1973- (The MIT Press, 2023)
"A new framework for critical data studies, aligned with media and digital literacies, that situates data literacy in broader debates on citizen agency and the democratic public sphere"--
Includes bibliographical references and index
Keywords: Digitalisierung; Datenkompetenz; Big Data; Daten; Gesellschaft; Informationsüberlastung; Alltag; Big data; Personal information management; Internet / Social aspects; Internet literacy; Données volumineuses; Gestion d'informations personnelles; Internet - Aspect social; Cyberculture; Internet - Social aspects